Fuzzy associative ℐ-ideals of IS-algebras - Eun Hwan Roh; Young Bae Jun; Wook Hwan Shim (International Journal of Mathematics and Mathematical Sciences)
We fuzzify the concept of an associative ℐ-ideal in an IS-algebra. We give a relation between a fuzzy ℐ-ideal and a fuzzy associative ℐ-ideal, and we investigate some related properties.